Cross-stitch before dying - Lee, Amanda, 1967- (Lee, Amanda, 1967- Embroidery mystery., 2013)
Marcy's mom Beverly is the costume designer for a lavish, Bollywood-style production and she suggests Tallulah Falls as a great place to shoot part of the film. Everyone at the embroidery shop, and around town, is in a flutter that a glamorous movie production is taking place in their midst. But when the star of the film is found murdered, the police suspect Marcy's mom, who made it no secret she did not care for the diva's attitude regarding her wardrobe. Marcy might as well issue an open call for suspects, because the star had a long list of enemies. To save her mom's career and keep her from accessorizing with handcuffs, Marcy and her friends will need to stitch together the clues to catch one crafty killer who may have designs on Marcy next.